Creating large EMS populations for functional genomics and breeding in wheat - Wenqiang Wang; Xizhen Guan; Yong Gan; Guojun Liu; Chunhao Zou; Weikang Wang; Jifa Zhang; Huifei Zhang; Qunqun Hao; Fei Ni; Jiajie Wu; Lynn Epstein; et al. (Journal of Integrative Agriculture, 2024)
Wheat germplasm is a fundamental resource for basic research, applied studies, and wheat breeding, which can be enriched normally by several paths, such as collecting natural lines, accumulating breeding lines, and introducing mutagenesis materials. Ethyl methane sulfonate (EMS) is an alkylating agent that can effectively introduce genetic variations in a wide variety of plant species. In this study, we created a million-scale EMS population (MEP) that started with the Chinese wheat cultivars 'Luyan 128', 'Jimai 38', 'Jimai 44', and 'Shannong 30'. In the M1 generation, the MEP had numerous phenotypical variations, such as >3,000 chlorophyll-deficient mutants, 2,519 compact spikes, and 1,692 male sterile spikes. There were also rare mutations, including 30 independent tillers each with double heads. Some M1 variations of chlorophyll-deficiency and compact spikes were inheritable, appearing in the M2 or M3 generations. To advance the entire MEP to higher generations, we adopted a single-seed descendent (SSD) approach. All other seed composites of M2 were used to screen other agronomically important traits, such as the tolerance to herbicide quizalofop-P-methyl. The MEP is available for collaborative projects, and provides a valuable toolbox for wheat genetics and breeding for sustainable agriculture.